The Utilization of New Media in the Establishment of Virtual Community: Trust Building and Self-Disclosure in the #WeAreHere Community - Ellya Pratiwi (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2021)
Virtual community is a new form of communication for digital society due to the potential use of new media. New media has led people to live in virtual reality. This study aims to determine the use of the Line application for #WeAreHere virtual community, to analyze the factors that encourage self-dislosure of community members, and to find out how community members build trust in the community. This research is a qualitative research using participatory observation method. Based on social exchange theory, the concept of self-disclosure and the trust building approach showed that self-disclosure and trust building are formed simultaneously. This research found that members' self-disclosures are driven by cost-benefit considerations. The benefits perceived by members from disclosure attitude are a feeling relieved or serenity and getting support from each other when interacting. The members' trust is formed because of trust in others through the attitudes and behavior of members, and trust in Line Square services on the Line application that provides anonymous features.